The Influence of Job Training, Organizational Culture, and Job Promotion on Employee Performance - Rismawati, R.; Herman, H.; Halim, Agus (Manunggal Halim Jaya, 2025)
This study investigates the impact of job training, organizational culture, and job promotion variables on employee performance at the Regional Office of the Ministry of Religious Affairs in West Sulawesi Province. The research method used is quantitative with primary data from a questionnaire. Respondents in this study were employees at the Regional Office of the Ministry of Religious Affairs of West Sulawesi Province, with a population of 200 employees. The sample used was the Probability Sampling technique, and the number of samples was determined using the Slovin formula with a sample size of 67 respondents. The formula in this study uses validity tests, reliability tests, multiple linear regression, t-tests, and F-tests. The results of this study indicate that job training and organizational culture variables have a partially significant effect on employee performance at the Regional Office of the Ministry of Religious Affairs of West Sulawesi Province. However, job promotion does not significantly affect the Regional Office of the Ministry of Religious Affairs of West Sulawesi Province. Then, the variables of job training, organizational culture, and job promotion have a significant and simultaneous effect on employee performance at the Regional Office of the Ministry of Religious Affairs of West Sulawesi Province.